2017
DOI: 10.1002/chem.201702643
|View full text |Cite
|
Sign up to set email alerts
|

A New Pathway for Protein Haptenation by β‐Lactams

Abstract: The covalent binding of β-lactams to proteins upon photochemical activation has been demonstrated by using an integrated approach that combines photochemical, proteomic and computational studies, selecting human serum albumin (HSA) as a target protein and ezetimibe (1) as a probe. The results have revealed a novel protein haptenation pathway for this family of drugs that is an alternative to the known nucleophilic ring opening of β-lactams by the free amino group of lysine residues. Thus, photochemical ring sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 62 publications
(21 reference statements)
2
10
0
Order By: Relevance
“…Interestingly, in the case of N ‐LAP, addition of the probes seems to generate greater constraint in the binding site, resulting in higher emission. This allosteric effect was previously observed with other drugs and site probes interacting with proteins, and it is mainly due to large conformational changes in the macromolecule upon ligand binding [18] …”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Interestingly, in the case of N ‐LAP, addition of the probes seems to generate greater constraint in the binding site, resulting in higher emission. This allosteric effect was previously observed with other drugs and site probes interacting with proteins, and it is mainly due to large conformational changes in the macromolecule upon ligand binding [18] …”
Section: Resultssupporting
confidence: 59%
“…This allosteric effect was previously observed with other drugs and site probesi nteracting with proteins, and it is mainly due to large conformational changes in the macromolecule upon ligand binding. [18] Finally,t he MD simulation studies carried out with the nearly non-emissive O-LAP@HSA binary complex revealed as imilar Figure 5. Binding mode of (A, B) LAP and (C,D) N-LAP with HSA protein obtained by MD simulation studies.…”
Section: Resultsmentioning
confidence: 83%
“…As expected, the more flexible part of the complex showed to be sub-domain IIIB, which is the one of the most accessible sub-domains of the protein that in the absence of ligand bounded undergoes conformational changes up to 10 Å. 19 Moreover, at the beginning of the simulation (the first ∼30 ns) a small displacement of the ligand was observed resulting from the Please do not adjust margins Please do not adjust margins initial adjustment of a large ligand into the structure. But eventually the ligand revealed to be stable during most of the simulation (∼170 ns).…”
Section: Molecular Modelling Studiessupporting
confidence: 70%
“…However, our results clearly showed that the main binding pocket of CPF is the cleft of the serum albumin "V" structure and not site II, as no covalent modifications of the aromatic residues of this pocket were observed in any of the six proteins studied. Reasoning that: (1) as observed in the crystal structure of HSA in complex with two molecules of ibuprofen (PDB code 2BXG, 21 2.7 Å), this cleft is located nearby to site II; and (2) the significant conformational changes that HSA can undergo upon binding ligands, specifically in domains I and III, as previously reported by Curry et al 22 and also by us 19 , we considered that the experimentally observed displacement of CPF by ibuprofen, which suggest site II as the main binding pocket, is also in agreement with the herein proposed binding. Thus, we believe that the higher affinity of ibuprofen than CPF to HSA and the expected conformational changes resulting of ibuprofen binding, in particular in the proximity of site II, might disfavor the binding of CPF to the "V" cleft of the protein.…”
Section: Molecular Modelling Studiesmentioning
confidence: 61%
“…In a parallel approach, molecular dynamics (MD) simulations can be used to study drug@biomolecule interactions (Spitaleri and Rocchia, 2019). Thus, properties such as the strength of interaction and the conformational orientation of a drug in the neighborhood of the amino acid residues of the protein binding sites can be investigated in detail (Pérez-Ruiz et al, 2017;Pinheiro and Curutchet, 2017;Molins-Molina et al, 2019;Spitaleri and Rocchia, 2019).…”
Section: Introductionmentioning
confidence: 99%